Tubulin detyrosination promotes human trophoblast syncytium formation. (13th August 2019) - Wang, Rui; Yu, Ruoxuan; Zhu, Cheng; Lin, Hai-Yan; Lu, Xiaoyin; Wang, Hongmei
Abstract: Human trophoblast syncytialization is one of the most important yet least understood events during placental development. In this study, we found that detyrosinated α -tubulin (detyr-α -tub), which is negatively regulated by tubulin tyrosine ligase (TTL), was elevated during human placental cytotrophoblast fusion. Correspondingly, relatively high expression of TTL protein was observed in first-trimester human placental cytotrophoblast cells, but fusing trophoblast cells exhibited much lower levels of TTL. Notably, fusion of preeclamptic cytotrophoblast cells was compromised but could be partially rescued by knockdown of TTL levels. Mechanistically, chronic downregulation of TTL in trophoblast cells resulted in significantly elevated expression of detyr-α -tub. Restoration of detyr-α -tub thus contributed to the cell surface localization of the fusogenic protein Syncytin-2 and the gap junction protein Connexin 43 (Cx43), which in turn promoted successful fusion between trophoblast cells. Taken together, the results suggest that tubulin detyrosination plays an essential role in human trophoblast fusogenic protein aggregation and syncytialization. Insufficient tubulin detyrosination leads to defects in syncytialization and potentially to the onset of preeclampsia.